PET imaging of neurodegenerative markers in Alzheimer's disease - Patrik Mattsson (2025)
Alzheimer's disease (AD) is a neurodegenerative disorder resulting in neuron loss and dementia. Pathophysiological changes take place years before clinical symptoms appear. The association of these brain changes with the development of the clinical syndrome of AD is not known in detail. Biomarkers for in vivo detection of early pathophysiological change in AD are needed for early diagnosis and may also have potential as targets for therapy and for monitoring of disease-modifying treatments. The overarching aim of the thesis projects was to explore the potential of positron emission tomography (PET) imaging of amyloid deposits, neuroinflammation and neuron loss for early detection of neurodegenerative changes in AD.The 18-kDa translocator protein (TSPO) is a biomarker of activated microglia and neuroinflammation in neurodegenerative disorders. In study I, 7 control subjects and 9 mild AD patients were examined with the high affinity second generation TSPO radioligand [18F]FEDAA1106 and an ECAT EXACT HR PET system. Binding of [18F]FEDAA1106 to TSPO in mild AD was not different from the binding in control subjects, neither in global grey matter nor in regional grey matter. The results may have been influenced by a TSPO gene polymorphism that was not known when the study was designed and conducted, resulting in an unknown prevalence of high and low affinity binders in the sample. The results may also have been influenced by the relatively high nonspecific binding of [18F]FEDAA1106, not allowing for detection of increased specific signal in the AD patients compared to the healthy controls. The conclusion of the study was that TSPO imaging with [18F]FEDAA1106 does not have potential for in vivo detection of microglial activation in mild AD.The serotonin 1A (5-HT1A) receptor is expressed at high levels in entorhinal cortex, hippocampus and amygdala, regions that are vulnerable to early neuron loss in AD. In study II, 8 control subjects and 7 mild AD patients were examined with the sensitive and specific 5-HT1A radioligand [11C]WAY100635 and the ECAT EXACT HR PET system as an approach to evaluate neurodegenerative changes in vivo. AD patients had lower binding of [11C]WAY100635 than control subjects in amygdala, entorhinal cortex and hippocampus. Our findings corroborate and extend previous results of decreased 5-HT1A binding in the medial temporal lobe in samples including moderate-severe AD patients, and we conclude that PET using [11C]WAY100635 has potential for sensitive assessment of neurodegeneration in mild AD.Accumulation of amyloid beta peptide (Aβ) deposits in the cerebral cortex is considered as an initiating step on the pathogenic pathway leading to AD. In study III, 10 elderly subjects with subtle longitudinal decline in episodic memory function and 10 age-matched subjects with stable episodic memory function were recruited from the population-based Betula study and examined with [11C]AZD2184, an Aβ radioligand with high sensitivity, and a high-resolution research tomograph (HRRT). We hypothesized that episodic memory decline, regarded as an early cognitive marker of AD, would predict cortical Aβ deposits. Contrary to our hypothesis, the binding of [11C]AZD2184 was higher in the stable group than in the declining group. The three highest individual binding potential values in the stable group were observed in carriers of the ApoE4 allele. We concluded that subtle episodic memory decline alone does not seem to predict Aβ pathology and may be caused by other underlying pathologies in this cohort.Results from post-mortem studies suggest that brain Aβ deposits appear in a sequence from isocortical to allocortical to subcortical regions. The early regional distribution of Aβ deposits, however, needs more detailed study in vivo. In study IV, 8 cognitively unimpaired (CU) subjects, 8 mild cognitive impairment (MCI) and 8 AD patients were examined with [11C]AZD2184 and the HRRT system. The main aim was to compare the presence of isocortical, allocortical and subcortical Aβ deposits with the results from previous post-mortem studies. Isocortical Aβ was detected in two thirds of the sample (3 CU, 5 MCI, 8 AD) and this group was the focus of the subsequent analysis. In these Aβ-positive subjects (n=16), Aβ was detected in striatum, thalamus and allocortex in 15, 14 and 10 subjects, respectively. We concluded that Aβ deposits seem to be widespread in early AD and that high contrast PET can be used for detailed study of the appearance of Aβ, which has implications for improved diagnostics and monitoring of disease-modifying treatments.List of scientific papersI. Varrone A, Mattsson P, Forsberg A, Takano A, Nag S, Gulyás B, Borg J, Boellaard R, Al-Tawil N, Eriksdotter M, Zimmermann T, Schultze- Mosgau M, Thiele A, Hoffmann A, Lammertsma AA, Halldin C. In vivo imaging of the 18-kDa translocator protein (TSPO) with [18F]FEDAA1106 and PET does not show increased binding in Alzheimer's disease patients. Eur J Nucl Med Mol Imaging. 2013 Jun;40(6):921-31. Epub 2013 Feb 22. PMID: 23436070. https://doi.org/10.1007/s00259-013-2359-1II. Mattsson P, Cselényi Z, Andrée B, Borg J, Nag S, Halldin C, Farde L. Decreased 5-HT1A binding in mild Alzheimer's disease-A positron emission tomography study. Synapse. 2022 Jun;76(7-8):e22235. Epub 2022 May 28. PMID: 35587913; PMCID: PMC9285435. https://doi.org/10.1002/syn.22235III. Mattsson P, Forsberg A, Persson J, Nyberg L, Nilsson LG, Halldin C, Farde L. β-Amyloid binding in elderly subjects with declining or stable episodic memory function measured with PET and [11C]AZD2184. Eur J Nucl Med Mol Imaging. 2015 Sep;42(10):1507-11. Epub 2015 Jun 27. PMID: 26115835. https://doi.org/10.1007/s00259-015-3103-9IV. Mattsson P, Cselényi Z, Forsberg Moren A, Freund-Levi Y, Wahlund LO, Halldin C, Farde L. High Contrast PET Imaging of Subcortical and Allocortical Amyloid-β in Early Alzheimer's Disease Using [11C]AZD2184. J Alzheimers Dis. 2024;98(4):1391-1401. PMID: 38552111; PMCID: PMC11091650. https://doi.org/10.3233/jad-231013